(untitled) (Research, Society and Development, 2021)
Objective: to propose the adoption of a specific drug kit for surgical procedures for decompression of the carpal tunnel, to replace the basic pharmacotherapeutic kit currently used. Methods: this is an experimental development project involving direct observation, administrative data collection, study of scientific evidence and economic comparison to propose the new kit. Results: direct observation indicated that the procedures adopted sometimes diverged from those based on scientific evidence; the profile of medication use showed that the current kit is underused and favors the irrational use of medications; knowing the usage profile and the scientific evidence, it was possible to propose a new, more economical kit, which allows to mitigate irrational use and contributes to patient safety strategies. Conclusion: the adoption of the proposed new kit can bring benefits to the institution both in terms of economy and contribution to better care outcomes and greater patient safety.